2005
DOI: 10.1002/ccd.20299
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde percutaneous aortic valve implantation for critical aortic stenosis

Abstract: Recently, a prosthetic aortic valve has been implanted percutaneously in several patients using an antegrade transseptal approach. This has been shown to be feasible and associated with dramatic hemodynamic improvement. We report a retrograde implantation of a percutaneous heart valve (PHV) in an 84-year-old man with critical aortic stenosis and refractory congestive heart failure after difficulties encountered with an initial antegrade approach. While attempting antegrade transseptal implantation of a PHV, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(36 citation statements)
references
References 13 publications
0
36
0
Order By: Relevance
“…Initial attempts at transarterial implantation with standard balloon valvuloplasty equipment were, however, compromised by difficulties negotiating the aortic arch and reaching and crossing the stenotic native valve, ultimately leading to abandonment of this approach (A. Cribier, MD, unpublished data, 2005). Recently, Hanzel et al 15 reported an antegrade procedure, which, when unsuccessful, was converted to a retrograde approach; however, mitral valve injury as a consequence of the antegrade component of the procedure led to cardiovascular collapse and death. Our experience suggests that with the use of equipment and techniques specifically designed for a transarterial approach, percutaneous aortic valve implantation can be accomplished routinely.…”
Section: Discussion Antegrade Versus Retrograde Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial attempts at transarterial implantation with standard balloon valvuloplasty equipment were, however, compromised by difficulties negotiating the aortic arch and reaching and crossing the stenotic native valve, ultimately leading to abandonment of this approach (A. Cribier, MD, unpublished data, 2005). Recently, Hanzel et al 15 reported an antegrade procedure, which, when unsuccessful, was converted to a retrograde approach; however, mitral valve injury as a consequence of the antegrade component of the procedure led to cardiovascular collapse and death. Our experience suggests that with the use of equipment and techniques specifically designed for a transarterial approach, percutaneous aortic valve implantation can be accomplished routinely.…”
Section: Discussion Antegrade Versus Retrograde Approachmentioning
confidence: 99%
“…14 Although a retrograde femoral arterial approach is an intuitive extension of aortic valvuloplasty technique, initial experiences were disappointing. 15 Antegrade femoral access problems relate not only to positioning the prosthesis across the stenotic, calcified aortic valve but also to delivery of the large-profile device and sheath through frequently diseased and tortuous femoral and iliac arteries and the abdominal and thoracic aorta. We describe our experience with the development of this procedure and the techniques and equipment designed to allow percutaneous retrograde transarterial implantation of aortic prosthetic valves.…”
Section: Editorials Pp 771 and 774mentioning
confidence: 99%
“…The technique has proved too complex for widespread dissemination, particularly with the firstgeneration device. Cribier also treated some patients with a retrograde transarterial approach, and Hanzel et al 53 reported the successful deployment of a percutaneous aortic valve through a retrograde approach. Conceptually simpler and more reproducible, reliable retrograde passage of the stent valve is facilitated by the introduction of a flexible, steerable delivery catheter.…”
Section: Clinical Trials Of Percutaneous Aortic Valvesmentioning
confidence: 99%
“…Both the Cribier-Edwards and CoreValve devices have been used in high-risk patients with predicted Euroscores Ͼ30%, with actual 30-day mortality rates Ͻ10%. [52][53][54][55][56] …”
Section: Clinical Trials Of Percutaneous Aortic Valvesmentioning
confidence: 99%
See 1 more Smart Citation